Antinuclear antibodies during procainamide treatment and drug acetylation. Issue 5985 (20th September 1975) - Davies, D M; Beedie, M A; Rawlins, M D
Abstract : Acetylator capacity was determined in two groups of patients who had received procainamide for more than three months. In seven patients antinuclear antibodies (A.N.A.) were detected during treatment, and these changes disappeared (in six patients) or were less pronounced (one patient) after withdrawal of the drug. These patients tended to have faster acetylation rates, and five were phenotypically "rapid" acetylators. Five patients who did not develop A.N.A. during treatment had less rapid (P less than 0.05) rates of acetylation, and four were "slow" acetylators. We suggest that the immunological changes which may occur during procainamide treatment may be associated with the acetylated metabolite of procainamide rather than the parent compound and that it might be possible to identify patients at risk.